THE ROLE OF CAPITAL STRUCTURE IN MODERATING FIRM GROWTH, FIRM SIZE AND INVESTMENT DECISION ON FIRM VALUE - Suci Kusuma Wardani; Eny Maryanti; Sarwenda Biduri (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the moderating role of capital structure on the effects of company growth, firm size, and investment decisions on the value of companies in the food and beverage industry in Indonesia. Method: A quantitative approach was applied, analyzing secondary data from companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. Results: The findings reveal that while company growth and firm size do not significantly impact firm value, investment decisions have a positive effect. Capital structure moderates the relationship between investment decisions and firm value positively and between firm size and firm value negatively. However, it does not moderate the effect of company growth on firm value. Novelty: This study contributes to literature by focusing on the food and beverage sector, using a recent data range and Eviews software for analysis, offering insights into the unique dynamics of capital structure within this industry.